1997
DOI: 10.1097/00002508-199709000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Pain Knowledge and Attitudes of Healthcare Providers: Practice Characteristic Differences

Abstract: Significant knowledge deficits regarding currently accepted principles of pain management practice as well as beliefs that could interfere with optimal care, mandate a need for educational interventions. Significant differences by profession, clinical practice area, and hospital setting reflect populations to be targeted for interventions. Unwarranted fear of addiction is a misunderstood and important concept that needs to be addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
102
1
6

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(116 citation statements)
references
References 24 publications
7
102
1
6
Order By: Relevance
“…In healthcare teams, cognitive diversity may be reflected in differences between members regarding knowledge of the patient or clinical situation, as well as experience of potential solutions to clinical problems. For example, in a study of knowledge related to pain, researchers found consistent and significant differences between healthcare professionals relating to indicators of pain as well as effects of subsequent drug administration and addiction risk (Lebovits et al, 1997). These knowledge differences are likely to generate dissimilar perceptions related to, for example, preferred solutions, which engender discussion of associated suggestions and motivate members to justify their own viewpoint and argue against those of others.…”
Section: Cognitive Diversity and Debate In Multidisciplinary Teamsmentioning
confidence: 99%
“…In healthcare teams, cognitive diversity may be reflected in differences between members regarding knowledge of the patient or clinical situation, as well as experience of potential solutions to clinical problems. For example, in a study of knowledge related to pain, researchers found consistent and significant differences between healthcare professionals relating to indicators of pain as well as effects of subsequent drug administration and addiction risk (Lebovits et al, 1997). These knowledge differences are likely to generate dissimilar perceptions related to, for example, preferred solutions, which engender discussion of associated suggestions and motivate members to justify their own viewpoint and argue against those of others.…”
Section: Cognitive Diversity and Debate In Multidisciplinary Teamsmentioning
confidence: 99%
“…These includes: attention given to and assessment of pain (Items 1, 4,6,11,12,13,15,16,21); Opioid related issues (Items 2, 5,8,10,17,18,19,20); General principles of pain management (Items 3,4,7,16,22); Pain management issues in children (Items 8 and 9); and Non-pharmacologic aspect of pain management (Item 14). As it is vividly seen some of the items are multidimensional assessing more than one domain of pain and its management.…”
Section: Study Toolsmentioning
confidence: 99%
“…The fact that pain management is one of the most important aspects of patient care and is most relevant to all nurses emphasize that the responsibility that rest on the shoulders of nurses for the comfort of patients far greater than that of other medical staffs (5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For one reason it is not mandatory to include any education on pain in pre-registration training and education. There have been numerous studies highlighting the inadequacies of pain content in the nursing curricula (Coulling 2005, McCaffery & Ferrell 1997, as well as other health professionals including medicine pharmacy (Lebovitz et al 1997), occupational therapy (Strong et al 1999) and physiotherapy (Scudds & Solomon 1995) across a variety of countries. A review of 50 nursing textbooks concluded that pain content was limited (Ferrell et al 2000).…”
Section: What Usually Happensmentioning
confidence: 99%